Kajian Terhadap Produksi Usaha Keramba Jaring Apung di Kelurahan Haranggaol Kabupaten Simalungun Provinsi Sumatera Utara - Anriani Simanjuntak; Hendrik; Tince Sofyani (Jurusan Sosial Ekonomi Perikanan, 2021)
The research was conducted in January 2020, in Haranggaol Village, Haranggaol Horison Sub-District, Simalungun Regency. The purpose of this study was to determine the production of Goldfish, Tilapia, and Catfish cultivated in KJA and to analyze the factors that affect business productivity in KJA. Research method is Survey, with quantitative analysis and Cobb Douglas were used to analyze the data of this study. The results showed that Tilapia production of 7.066 bags of cages was 18.856,3 tons/year, Goldfish production of 84 bags of cages which were polyculture was 145,6 tons/year and Catfish production of 9 bags of cages was 14,17 tons/year. Every farmer in this village was harverst for Goldfish and Tilapia twice for a year and Catfish three times for year. Each harvest, the Tilapia weight was 250-500 gr/fish, Goldfish 500-600 gr/fish, and Catfish 250 gr/fish. The selling price of Tilapia was IDR.22.000,-/kg, Goldfish IDR.28.000,-/kg, and Catfish IDR.12.000,-/kg. The results showed that the factors that affect productivity were seeds, feed, and the number of cages. The result shows that simultaneously there was a significant affect of these three factors to the productivity of the fish. Partially the factors of seeds and feed production were significant, while the number of cages had no significant affect. The regression result showed the value of Adjusted R Square is 0,0898 or 89%, and it can be concluded that 89% of the total fish production in KJA was based on the factors of seed production (X1), feed (X2), and the number of cages (X3), and the rest 11% are variables outside of this research.